二酸化炭素分圧測定ブイを用いた南極海域の観測の予備的結果 - 渡邉, 修一; 中野, 善之; 飯田, 高大; 高村, 友海; 脇田, 昌英; Shuichi, Watanabe; Yoshiyuki, Nakano; Takahiro, Iida; Tomomi, Takamura; Masahide, Wakita (2013)
The total ocean uptake flux including the anthropogenic CO2 was estimated to be 2.0±1.0Pg-C/yr in a reference year 2000 by Takahashi et al.(2009). However, contribution of the seaonal ice-freezone in the southern ocean was about 0.06 Pg-C/yr. This estimate flux was smaller than that estimeted previously by Takahashi et al.(2002). Though Lenton, Matear and Tilbrook (2006) suggested sampling regularly every 3 months, at every 30 degree in longitude and 3 degree in latitude is sufficient to determine the net Southern Ocean CO2 uptake which uncertenly has less then 0.1PgC/yr, This difference is due to the luck of data in the southern ocean. In this study, we distributed the pCO2 autonomous buoy systems to collect a lot of pCO2 data, which sysmtem was devloped with the support of the Japan EOS Promotion Program (JEPP), the Ministry of Education, Culture, Sports, Science and Technology (MEXT). The pCO2 autonomous buoy system was deplyed at 50.5, 53, 56, and 59oS along 110oE and 60.5 oS, 70 oE near Kerguelen Plateau December, 2012 using the icebreaker “Shirase”. Those bouys are setting 8 times pCO2 measurements/day, 5days interval. The bouys are floating over our expected area with wind driving. The pCO2 values obtained till March 2013 are between 250 and 450μatm and comparative with other data. This preliminary data will be examined carefuly and used for discussing the distribution of pCO2. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 統計数理研究所 ３階セミナー室１（D305） conference object